„How to make a needle to float?” Heuristic-branched e-model of an animated movie utilized for class work - HILCENKO, Slavoljub (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
An animated movie does not require any motivation for watching it. That is why it is very useful as the learning source at elementary school class work. The aim of this work is promotion of the heuristic-branched learning model on the example of the animated movie with direct manipulation of the animated content. The represented example of this „little scientific” animated e-task should instigate functional thinking and the model can be applied at each and every school subject.